Fabry cardiomyopathy: Gb3‐induced auto‐reactive panmyocarditis requiring heart transplantation. (29th April 2020) - Frustaci, Andrea; Scarpa, Maurizio; Maria da Riol, Rosalia; Agrati, Chiara; Finato, Nicoletta; Verardo, Romina; Grande, Claudia; Chimenti, Cristina; Di Nora, Concetta; Russo, Matteo Antonio; Livi, Ugolini
Abstract: Resistance to enzyme replacement therapy (ERT) is a major therapeutic challenge in Fabry disease (FD). Recent reports attribute to immune‐mediated inflammation a main role in promoting disease progression and resistance to ERT. Aim of the study is to report a Gb3‐induced auto‐reactive panmyocarditis causing inefficacy of ERT and severe electrical instability, which required cardiac transplantation. Examining the explanted heart from a 57‐year‐old man with FD cardiomyopathy (CM) on 3‐year ERT presenting incoming ventricular fibrillation, we documented a severe virus‐negative myocarditis extended to cardiomyocytes, intramural coronary vessels, conduction tissue, and subepicardial ganglia. Serology was positive for anti‐Gb3, anti‐heart, and anti‐myosin antibodies. In vitro Gb3 stimulation of patient's peripheral blood mononuclear cells (PBMC) induced high amount production of inflammatory cytokine IL1‐β, IL‐6, IL‐8, and TNF‐α. PBMC were stained using the monoclonal antibodies CD3‐V500, CD4‐V450, CD8‐APCcy7, CD45RO‐PerCPcy5.5 and CD27‐FITC from BD Biosciences and CD56‐PC7 from Bekman Coulter. The phenotypic analysis of PBMC showed a lower frequency of CD8 (9.2%) vs. 19.3% and NKT cells (1.6% vs. 2.4%) in Fabry patient respect to healthy donor, suggesting a possible homing to peripheral tissues. A Gb3‐induced auto‐reactive myocarditis is suggested as a possible cause of FDCM progression and ERT resistance. Immune‐mediated inflammation of systemic Fabry cells may coexist and be controlled by implemental immunosuppressive therapy.